Strategi Pesantren dalam Pemberdayaan Masyarakat pada Era Generasi 4.0 - Imam Alfi (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
The presence of pesantren together with the birth of the Indonesian nation has a major contribution to the direction of the Indonesian nation. The uniqueness and maturity of pesnatren can pass from one period to another. Islamic boarding school has a dual role, namely as a display of the face of Islam that is polite and peaceful. The next role is as unique to the original Indonesian education model. Entering the era of Pesantren 4.0 there are more complex challenges. Pesantren is not only an asset of Indonesia but a global asset. So pesantren must open themselves by preparing a strategy to reach the era of 4.0. This research is a library research with a qualitative descriptive approach. Sources of data obtained through library search and analyzed through content analysis so that it becomes a complete and comprehensive conclusion. the results of the study are that the pesantren's strategy in portraying itself in the current era is first; The pesantren remains committed and istiqomah in its uniqueness and uniqueness that is to deepen the knowledge of religion (Tafaqquh fi Alddin) accompanied by practice in the lives of students as has been proven so far. In addition pesantren must expand to the wider outside world, namely as an agent of national and international peace (Rahmatal lil alamin) as aspired by Islam. The last one is making pesantren as an agent of community empowerment that grows and develops and is owned by the community. Pesantren need to make social engineering that leads to the function of pesantren as an enabler, empowerment and community protector